Mémoires d’immigrés, mémoires de France? Mémoires et reconnaissance - Marine Corde (Conserveries Mémorielles)
Immigration seems to be a subject rarely dealt with in French history; it is considered more as something functional rather humanitarian (the immigrant is often seen only as a worker.) However one only needs to look a bit closer into history to discover that immigration to France is a very old element, which has played a part in the development of France not only economically but also politically, socially and culturally. These last years, following the creation of a Cité Nationale de l’Histoire de France in Paris, numerous initiatives have been elaborated to develop this primordial theme. This article looks into one of these projects which tries to emphasize the importance of the immigrants’ function in the formation of the French society. It follows the activities of a NGO in the Rhône-Alpes which hopes, with the help of young people aged from 12 to 25, to present the memoirs of immigrants as part of the nation’s cultural heritage. Through this process, how do these young people represent immigration in France? Which images of France and of the immigrants are depicted? How are the immigrants’ words linked to the message the NGO wishes to transmit? This is what I would like to explain in this article.